Inhibition of ACOX1 enhances the therapeutic efficacy of obeticholic acid in treating non-alcoholic fatty liver disease and mitigates its lipotoxicity - Yang, Yuping; Yuan, Weinan; He, Kun; Lin, Chuangzhen; Du, Shenshen; Kou, Yanqi; Nie, Biao (Frontiers in Pharmacology, 2024)
Background and aims: High-dose Obeticholic acid exhibits promise for non-alcoholic fatty liver disease (NAFLD) treatment but can induce lipotoxicity. Our study sought to understand this mechanism and propose a solution. Approach and Results: In a non-alcoholic fatty liver disease (NAFLD) model induced by a high-fat diet in FXR-/- mice, we pinpointed that FXR regulated the expression of ACOX1 through RNA-Seq analysis. In the livers of FXR-/- mice, both ACOX1 mRNA and protein expression notably decreased. In both HL-7702 and HEP-G2 cells, the silencing of FXR through shRNA plasmids decreased ACOX1 expression, while FXR activation with GW4064 increased it. These effects were reversible with the ACOX1-specific inhibitor, 10,12-Tricosadiynoic acid. In the NAFLD model of FXR-/- mice, The activation of ACOX1 is correlated with elevated serum LDL, triglycerides, and aggravated hepatic steatosis. However, the combination of 10,12-Tricosadiynoic acid with low-dose obeticholic acid effectively treated hepatic steatosis, reducing LDL levels in the NAFLD model of wild-type mice. This combination therapy demonstrated efficacy comparable to high-dose obeticholic acid alone. Notably, the combined drug regimen treats hepatic steatosis by inhibiting the IL-1β and α-SMA pathways in NAFLD. Conclusions: Combining ACOX1-specific inhibitors with low-dose obeticholic acid effectively treats high-fat diet-induced hepatic steatosis and reduces serum LDL. This approach enhances the therapeutic effects of obeticholic acid and mitigates its lipotoxicity by inhibiting the IL-1β and α-SMA pathways.